High-performance work practices, career satisfaction, and service recovery performance: a study of flight attendants - Karatepe, Osman M.; Vatankhah, Sanaz (Emerald Group Publishing Ltd, 2015)
Purpose - The purpose of this paper is to propose and test a conceptual model that examines career satisfaction (CSAT) as a mediator of the effects of high-performance work practices (HPWPs) on service recovery performance, drawing from social information processing and Bagozzi's (1992) reformulation of attitude theories. Design/methodology/approach - Data were gathered from flight attendants, with a time lag of two weeks in the private airline companies in Iran. The relationships were gauged using structural equation modeling. Findings - The results suggest that career opportunities seem to be the most important indicator of HPWPs, followed by rewards, selective staffing, empowerment, teamwork, job security and training. The results further suggest that the availability of HPWPs boosts flight attendants' CSAT and that, in turn, results in elevated levels of service recovery performance. Originality/value - This study contributes to the current literature by linking HPWPs, as manifested by selective staffing, job security, training, empowerment, rewards, teamwork and career opportunities, to service recovery performance through CSAT based on data obtained from flight attendants.
Keywords: Career satisfaction; Iran; Airlines; High-performance work practices; Service recovery performance; Flight attendants